CGIAR Platform for Big Data in Agriculture Annual Report 2020 - CGIAR Platform for Big Data in Agriculture (2021)
The Platform completed its fourth year as a CGIAR global digital practice, demonstrating that open data standards, sharing, and analytic infrastructure; partnerships and communities of practice; and applied innovation strategy reinforce each other to accelerate inclusive, impactful digitization in agricultural development. In 2020, BIG DATA brokered 72 external partnerships to drive digital innovation in research and unlock data sharing across public, private, and non-profit organizations; and delivered 22 digital innovations and policies to build new digital impact pathways for CGIAR research.